Formula Cerita Detektif dalam Novel Yogisha X No Kenshin Karya Keigo Higashino - Putri, Tiara Rosmika; Anwar, Fithyani; Taqdir, Taqdir; Nurfitri, Nurfitri (HUMANIKA, 2025)
This study analyzes the application of the classical detective formula in Keigo Higashino’s novel Yogisha X no Kenshin using John George Cawelti’s theory of the classical detective formula. The purpose of this research is to identify the narrative patterns and their modifications that distinguish the novel from conventional detective formulas. The study employs a descriptive qualitative method with a close-reading technique. The data were obtained from the Japanese version of the novel and its Indonesian translation, then classified according to the five aspects of the classical detective formula: introduction of the detective, crime and clues, investigation, announcement of the solution, explanation of the solution, and the ending. The findings show that although the classical detective formula is applied consistently, it is accompanied by structural innovations. The story does not begin with the introduction of the detective, but instead opens with the depiction of a crime supported by false clues functioning as diversions. The character Yukawa Manabu is portrayed as a physics professor who solves the case through a scientific approach. The investigation process highlights not only the criminal aspects but also the moral conflicts accompanying the perpetrator’s actions. The stages of announcing and explaining the solution, together with the ending, are presented sequentially and form a confrontational structure in revealing the true perpetrator. Yogisha X no Kenshin enriches the detective genre by modifying the classical formula through scientific reasoning, clue manipulation, and nuanced characterization of the perpetrator. Such innovations represent an important contribution to the development of modern detective formulas in Japan.